Reflexiones en torno al 11 de septiembre de 2001 y el ineludible deber de elegir - Rodriguez Arocho, Wanda C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
It was November 22, 1963. I clearly remember when my father opened the door that leads from our convenience store into our living room and said: "Kennedy was shot". I remember my mother coming out of the kitchen in a hurry while arguing with my father about his bad habit of joking about everything because that joke "was the last straw". I do not remember what my father replied if he ever did. I only remember him walking faster toward the TV set, and turning it on. As I watched the images on the TV news, as well as my father and mother's reaction, I tried to understand what was happening. I was trying to figure it out with the cognitive skills of an II year old girl.